ChemInform Abstract: Cu‐Mediated 1, 3‐Dipolar Cycloaddition of Azomethine Ylides with Dipolarophiles: A Faster Access to Spirooxindoles of Potential Pharmacological Interest. Issue 4 (28th January 2014) - Singh, Shambhu Nath; Regati, Sridhar; Paul, Abir Kumar; Layek, Mohosin; Jayaprakash, Sarva; Reddy, K. Venkateshwara; Deora, Girdhar Singh; Mukherjee, Soumita; Pal, Manojit
Abstract The first Cu‐mediated one‐pot three‐component reaction of isatin derivatives (I), L‐proline (II), and terminal alkynes (III) leading to spiropyrrolidine oxindols (IV) is reported.